2020
DOI: 10.1016/j.anaerobe.2020.102233
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Clostridioides difficile infection (CDI): Possible implications for elderly patients

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 22 publications
1
32
0
11
Order By: Relevance
“…The major strength of our study is that, to our knowledge, it is the first one to report on a considerably higher rate of CDI in hospitalized patients during the pandemic. Even though the probability of this has always been regarded as high and has been speculated upon [34], the high rate of CDI and COVID-19 coinfection still remains unproven. We acknowledge that the findings of our study are in contrast to other recent publications, one of which reported a lower incidence of CDI [21], while another a similar incidence of CDI [20] among patients with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The major strength of our study is that, to our knowledge, it is the first one to report on a considerably higher rate of CDI in hospitalized patients during the pandemic. Even though the probability of this has always been regarded as high and has been speculated upon [34], the high rate of CDI and COVID-19 coinfection still remains unproven. We acknowledge that the findings of our study are in contrast to other recent publications, one of which reported a lower incidence of CDI [21], while another a similar incidence of CDI [20] among patients with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 1 (SARS), Middle East Respiratory Syndrome (MERS), and severe acute respiratory syndrome coronavirus 2 (COVID-19) have also been associated with bacterial resistance coinfections [ [64] , [65] , [66] ]. Most deaths in the 1918 influenza pandemic were due to secondary bacterial infections, predominately Streptococcus pneumoniae [ [67] , [68] , [69] ].…”
Section: Resultsmentioning
confidence: 99%
“…The increased use of antibiotics to treat COVID-19 may, inadvertently, have resulted in an under-reporting of C. difficile infection. Actually, Spigaglia ( 2020 ) has published an article expressing her opinion about the COVID-19 and the impact in elderly patients, who will probably become more susceptible to CDI. The author also demonstrates her concern about the low number of bacterial infections cases related to patients with Sars-Cov-2.…”
Section: Discussionmentioning
confidence: 99%